ALMOST ALL SETS OF d+2 POINTS ON THE (d‐1)‐SPHERE ARE NOT SUBTRANSITIVE. Issue 2 (28th March 2013) - Eberhard, Sean
Abstract: We generalise an argument of Leader, Russell, and Walters to show that almost all sets of d + 2 points on the ( d ‐ 1 ) ‐sphere S d ‐ 1 are not contained in a transitive set in some R n .